What Is the Potential of Daphnia (Water Flea) Predation as a Means of Biological Suppression of Prymnesium parvum (Golden Algae) Blooms in Ecologically Relevant Conditions? - Marta Galas; Marta Grabska; Maksymilian Zienkiewicz; Tomasz Krupnik (Plants)
This study explores the interaction between Prymnesium parvum and Daphnia magna under low-salinity conditions. P. parvum showed reduced growth below 0.4 PSU and peaked at 1.0 PSU within the tested 0.2–1.0 PSU range. D. magna, exposed to P. parvum across 0.0–6.0 PSU, experienced increased mortality at 4.0 and 6.0 PSU, but tolerated 0.0–1.0 PSU well and grazed actively on P. parvum without significant vitality loss. This range reflects conditions observed in the Oder River during the 2022 fish die-off. The count of P. parvum cells did not vary significantly across the 0.2 to 1.0 PSU range of salinities in D. magna presence, except at 0.6 PSU. All daphnids survived even at P. parvum densities of 1 × 105 cells/mL, though increasing algal concentrations reduced juvenile growth rates. Direct observation under a microscope confirmed algal ingestion. Toxin accumulation in cells and medium likely reduced grazing efficiency via allelopathic effects. The study assessed whether D. magna can tolerate prymnesins while maintaining feeding under varying salinities. Results suggest that Daphnia magna could act as a biological suppressor of golden algae under certain environmental conditions, though further work is needed to quantify grazing efficiency and prymnesins concentrations.